1201 The Impact of a Spinal Best Practice Tariff on Compliance with The British Spine Registry. (12th October 2021) - Rajgor, H; Habbebulah, A; Gardner, A; Jones, M
Abstract: Aim: The British Spine Registry (BSR) was introduced in May 2012 to be used as a web-based database for spinal surgeries carried out across the UK. In 2019 NHS England and NHS Improvement introduced a new Best Practice Tariff (BPT) to encourage input of spinal surgical data on the BSR. The aim of our study was to assess the impact of the spinal BPT on compliance with the recording of surgical data on the BSR. Method: A retrospective review of data was performed at a tertiary spinal centre, Royal Orthopaedic Hospital Birmingham, between 2018-2020. 3587 patients were included in our study. Data was collated from electronic patient records, theatre operating lists and trust specific BSR data. Results: 1684 patients were eligible for BPT. In 2018-19 269/974 (28%) records were complete on the BSR for those that would be eligible for BPT. Following introduction of BPT in 2019, 671/710 (95%) records were complete having filled in the mandatory data (P < 0.01). Patient consent to data collection also improved from 62% to 93%. Email details were present in 43% of patients compared with 68% following BPT introduction. Conclusions: Our study found that following the introduction of a BPT, there was a statistically significant improvement in BSR record completion compliance in our unit. The BPT offers a financial incentive which can help generate further income for trusts. National data input into the BSR is vitally important to assess patient outcome following spinal surgery. The BSR can also aid future research in spinal surgery.